2019
DOI: 10.1098/rsos.190127
|View full text |Cite
|
Sign up to set email alerts
|

Ageratina adenophora causes spleen toxicity by inducing oxidative stress and pyroptosis in mice

Abstract: Ageratina adenophora is an invasive weed with potent toxicological effects on livestock. Oxidative stress and pyroptosis play a pivotal role in regulating animal or human health and disease. The object of this study was to determine the mechanism underlying splenic toxicity induced by A. adenophora in a mouse model. Ageratina adenophora significantly increased the levels of reactive oxygen species and malondialdehyde, but decreased the antioxidants li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…Researchers have studied the main toxic substances, target organs, and toxic effects of A. adenophora , and found that A. adenophora mainly affects the liver and spleen [ 21 ]. This result was in agreement with other studies of A. adenophora leaf toxicity [ 11 , 15 , 18 , 34 ]. In the current study, the leaves of A. adenophora were evaluated for their ability to induce toxicity in the spleen of hosts ingesting them (as a powder) in their standard diet.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Researchers have studied the main toxic substances, target organs, and toxic effects of A. adenophora , and found that A. adenophora mainly affects the liver and spleen [ 21 ]. This result was in agreement with other studies of A. adenophora leaf toxicity [ 11 , 15 , 18 , 34 ]. In the current study, the leaves of A. adenophora were evaluated for their ability to induce toxicity in the spleen of hosts ingesting them (as a powder) in their standard diet.…”
Section: Discussionsupporting
confidence: 93%
“…Both normal and experimental feed were shaped into a pellet with a cylindrically-shaped tube, with a diameter of 2 cm and height of 5 cm. as in Sun et al’s study [ 18 ].…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…A. adenophora has been reported to induce hepatotoxic effects on various organs of animals (Oelrichs et al, 1995;Katoch et al, 2000;Sun et al, 2019). Euptox A (9-oxo-10, 11-dehydroageraphorone) is one major cadenine sesquiterpene toxin of A. adenophora leaves (Fig.…”
Section: Introductionmentioning
confidence: 99%